2014
DOI: 10.1590/s0100-736x2014000200007
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade do leite de vacas criadas no sistema silvipastoril no Vale do Cauca, Colômbia

Abstract: O sistema silvipastoril caracteriza-se por aumentar a produção de leite, com maior número de vacas por hectare devido ao maior aporte de proteína na dieta. Neste sistema as vacas são alimentadas, além do pasto, de pequenas árvores e arbustos. O objetivo do presente estudo foi determinar os principais indicadores de qualidade do leite e agentes causais de mastite em vacas criadas em sistema silvipastoril. Foram avaliadas a composição (teor de gordura, proteína total, lactose, extrato seco, extrato seco desengor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The results obtained for isolated species in the microbiological culture of 177 lactating cow's milk samples showed the occurrence of important mastitis pathogens and are presented in Table 1. The predominance of the genus Staphylococcus agrees with other prevalence studies conducted in both Brazilian dairy herds and in dairy farms in other countries (Nader Filho et al 2007, Bolaños et al 2014.…”
Section: Mastitis Etiologysupporting
confidence: 90%
“…The results obtained for isolated species in the microbiological culture of 177 lactating cow's milk samples showed the occurrence of important mastitis pathogens and are presented in Table 1. The predominance of the genus Staphylococcus agrees with other prevalence studies conducted in both Brazilian dairy herds and in dairy farms in other countries (Nader Filho et al 2007, Bolaños et al 2014.…”
Section: Mastitis Etiologysupporting
confidence: 90%
“…Studies have demonstrated in vitro microbial resistance of strains isolated from cow's milk of 30% to the drug ampicillin (Bolaños et al, 2014;Siqueira et al, 2014).…”
Section: Resultsmentioning
confidence: 99%